Poligami dalam Al Qur’an Surat An-Nisa’ Ayat 3 Perspektif Kitab Tafsir Al-Azhar Karya HAMKA - Andressa Muthi’ Latansa (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2023)
This study discusses polygamy in the perspective of Hamka. Polygamy is a man who has a wife more than one up to four people. In Islamic view, polygamy can be done if it meets the requirements that are clearly mentioned in the Qur'an, that is, being able to be fair. The fair referred includes several parts, namely: fair in the shared time, fair in living, fair in the place of residence and fair in the cost of the child. Rasulullah's polygamy is different from the polygamy phenomena that we face today. The practice of the Prophet's polygamy is not based on biological needs, but there are several considerations including wanting to honor the widow, raising the degree of widows and women who offer herself to be married. In the present, polygamy is based solely on biological needs, and lose the element of justice in it.